2009
DOI: 10.1161/circulationaha.108.799403
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcome After a First Angiographically Confirmed Coronary Stent Thrombosis

Abstract: Background-There are limited data on the long-term clinical outcome after an angiographically confirmed (definite) stent thrombosis (ST). Methods and Results-Four hundred thirty-one consecutive patients with a definite ST were enrolled in this multicenter registry. The primary end point was the composite of cardiac death and definite recurrent ST. Secondary end points were all-cause death, cardiac death, definite recurrent ST, definite and probable recurrent ST, any myocardial infarction, and any target-vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
4
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 15 publications
4
86
4
8
Order By: Relevance
“…In contrast, the present study also demonstrated that the clinical outcomes of stent thrombosis were similar between DES and BMS implantation, as reported in previous studies. 9 This finding was observed in EST, LST, and VLST. The present results suggest that coronary artery bypass grafting is considered early in patients with recurrent ischemic events after PCI for EST and LST, whether after DES or BMS implantation.…”
Section: Kubo S Et Almentioning
confidence: 65%
See 1 more Smart Citation
“…In contrast, the present study also demonstrated that the clinical outcomes of stent thrombosis were similar between DES and BMS implantation, as reported in previous studies. 9 This finding was observed in EST, LST, and VLST. The present results suggest that coronary artery bypass grafting is considered early in patients with recurrent ischemic events after PCI for EST and LST, whether after DES or BMS implantation.…”
Section: Kubo S Et Almentioning
confidence: 65%
“…6,8, 9 The predictors of the composite of cardiac death and non-fatal myocardial infarction, such as post-procedural TIMI flow grade <3 and low left ventricular ejection fraction, stent sites were the other independent predictors of TLR. VLST was an independent negative predictor of the composite of cardiac death and non-fatal myocardial infarction (HR, 0.34; 95% CI: 0.16-0.73, P=0.006).…”
Section: Kubo S Et Almentioning
confidence: 97%
“…One study showed unfavorable long-term clinical outcomes after definite stent thrombosis, which were associated with diabetes mellitus, left ventricular ejection fraction <45%, long total stent length, complex coronary lesions, TIMI flow grade <3 after PCI, and implantation of an additional coronary stent during primary PCI. 7 Our study also dealt with long-term clinical results, but focused on angiographically-defined VLST and not acute or subacute thrombosis; the results were also unfavorable with a 16% MACE rate and a 50% restenosis rate. It might be interesting to compare acute and subacute ST patients with late ST patients; however, data are scarce because of the rare incidence of ST, and therefore a large study would be needed.…”
Section: Discussionmentioning
confidence: 99%
“…ST is associated with higher risk of experiencing MI and death, both components of the composite clinical end point. 45 The absence of consistent association with clinical end points might indicate that the alleles have no impact on distant outcomes such as MI and death and that the significant effect of ST is diluted when combining the various end points. Liu et al had performed meta-analyses on the separate clinical end points, such as bleeding complications, MI, stroke, and death, and found that effect sizes ranged from 0.99 to 1.55, with the exception of 2.37 for stroke.…”
Section: Discussionmentioning
confidence: 99%